Environmental analysis of quasi-static electric field changes of tropical lightning flashes - Mohamad Sabri, Muhammad Haziq; Ahmad, Mohd Riduan; Periannan, Dinesh; Seah, Boon York; Yusop, Norbayah; Mohd Esa, Mona Riza; Mohammad, Sulaiman Ali; Abdul-Malek, Zulkurnain; Lu, Gaopeng; Zhang, Hongbo; Cooray, Vernon; Al-Kahtani, Ammar Ahmed; et al. (Cevkor Vakfi, 2019)
The environmental conditions leading to the bouncing-wave discharge and the subsequent electron beam remain to be investigated in more detailed future studies. The analysis of quasi-static initial electric field changes (IECs) were found at the beginning of all 24 lightning flashes detected within reversal distance (22 Negative Cloud-to-Ground (–CG) and 2 normal Intra-Cloud (IC) flashes) in a tropical storm on June 15th, 2017 close to our station in Malacca, Malaysia (2.314077° N, 102.318282° E). The IECs durations averaged 4.28 ms for –CG flashes (range 1.48 to 9.45 ms) and averaged 11.30 ms for normal ICs flashes (range 7.24 to 15.35 ms). In comparison to Florida storms, the duration of IECs for –CG and IC flashes were 0.18 ms (range 0.08 to 0.33 ms) and 1.53 ms (range 0.18 to 5.70 ms), respectively. Moreover, the magnitudes of E-change for tropical thunderstorm were 0.13 V/m (range 0.03 to 0.44 V/m) for –CG flashes and-0.20 V/m (range-0.13 to-0.27 V/m) for IC flashes. The E-change magnitudes of tropical flashes are significantly larger than Florida flashes.